The creation of spin off as a learning strategy - Inga Llanez, Elvia Rosalía; Yaguache Aguilar, María Fernanda (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Starting in the 20th century, there has been a paradigm shift in the teaching-learning process with the support of new technologies. The name of Spin Off is added to the creation of a company, which allows the exploitation of research and practical knowledge of the students. Its creation is based on the process of setting up Simplified Stock Companies (SAS) and a parallel model of double entry (knowledge/practice) for the academic development of Advanced Financial Accounting. The students respond to this initiative with empowerment of the obligations assigned both at the operational, accounting and fiscal application level.